RESEPSI UMAT ATAS ALQURAN: MEMBACA PEMIKIRAN NAVID KERMANI TENTANG TEORI RESEPSI ALQURAN - Riyadi, Fahmi (Hunafa: Jurnal Studia Islamika, 2014)
Abstract. The Arab society has a great cultural memory, especially in language. This cultural identity has become a very accommodating identity over the revelation of the Koran. Therefore, it is not strange whenever in many stories, when recepting the Koran, the early Muslim community had a tremendous fascination. This is very different from non-Arab people. There is a kind of unity that spawned an amazing and entrancing experience. Nevertheless, the reception of the later muslims over the Koran have been evolving. The shift of culture and of paradigm, and how the Quran is presented is the main reason. The estestis reception of Muslims over the Koran -especially those living in the time of the Prophet-, attracted the attention of Navid Kermani. It is the issue which will be reviewed in this article.Kata Kunci: resepsi, bahasa, Alquran, memori kultural, Kermani